Bactericidal Activity of Multiple Combinations of Tigecycline and Colistin against NDM-1-Producing Enterobacteriaceae - Albur, Mahableshwar (American Society for Microbiology, 2012)
The interaction between colistin and tigecycline against eight well-characterized NDM-1-producing Enterobacteriaceae strains was studied. Time-kill methodology was employed using a 4-by-4 exposure matrix with pharmacokinetically achievable free drug peak, trough, and average 24-h serum concentrations. Colistin sulfate and methanesulfonate alone showed good early bactericidal activity, often with subsequent regrowth. Tigecycline alone had poor activity. Addition of tigecycline to colistin does not produce increased bacterial killing; instead, it may cause antagonism at lower concentrations.